Analysis of restricted antibiotics’ implementation in Clinical center of Montenegro during 2019. and the impact of COVID-19 epidemic on their usage - Lukač, Džana; Miljković, Branislava (Archives of Pharmacy, 2022)
In 2016, Clinical center of Montenegro filed a restriction on implementation of amikacin, tobramycin, ceftazidime, cefotaxime, cefixime, cefepime, colistin, linezolid, moxifloxacin, ofloxacin, levofloxacin, meropenem, imipenem/cilastatin, ertapenem, piperacillin/tazobactam, tigecycline, vancomycin and teicoplanin. The goal of this research is analysis of restricted antibiotics’ implementation during 2019. and their usage during the COVID-19 epidemic. 174 requests for restricted antibiotics from 2019. and the usage of restricted antibiotics during the COVID-19 pandemic were retrospectively analyzed. By data analysis it was determined that the antibiogram has been done only in 21,84% of cases. In 72.25% of cases restricted antibiotic was included in therapy without prior antimicrobial therapy using unrestricted antibiotic. Monotherapy was included in 75,28% of cases, two antibiotics were used in 19,54% of cases, combination of three in 4,02% of cases, and there were 1,15% of cases of using 4 restricted antibiotics in therapy. Most commonly used antibiotics were meropenem (53 cases – 30,45%), amikacin (36 cases – 20,68%), vancomycin (33 cases – 18,7%). The combination of imipenem and cilastatin was used in 13 cases (7,47%). Most commonly isolated causative agents were Acinetobacter spp. (8), Pseudomonas aeruginosa (8), Staphylococcus aureus (6) and Clostridium difficile (4). Usage of restricted antibiotics has increased during COVID-19 (2021) – usage of amikacin has risen 1,5 times more than in 2019, ceftazidime 2,3 times, cefixime 1,6, meropenem 2,3, piperacillin/tazobactam 2,57 and vancomycin 1,63 times.The increase of restricted antibiotics’ usage during COVID-19 could highly negatively affect rational antibiotic use implementation, as well as the antimicrobial resistance.